Towards data-driven salt marsh habitat conservation: A study from the southeast coastal ecosystem of Bangladesh - Sarker, Subrata; Nahiduzzaman, Md; Riya, Shashowti; Hossain, Md. Shahadat; Mokarrom, Hossain; Das, Nabanita; Uddin, Sharif; Alam, Sunjida; Tethe, Most. Jarin (Elsevier, 2025)
Salt marsh ecosystems are vital for coastal protection, biodiversity support, and carbon sequestration, while also serving as nurseries for coastal and marine species and improving water quality. This study assessed the extent and ecological significance of the salt marsh ecosystem along the southeast coastal zone of Bangladesh. In addition, the study explored the biota associated with salt marshes, identified anthropogenic stressors affecting them and proposed conservation options. A citizen science-based monitoring approach, along with the scientific sampling, was conducted between July 2023 and June 2024 to collect the data from the study area. The study identified a 34 km-long salt marsh habitat extending from Sitakunda to Kattoli beach along the Chattogram coast of Bangladesh. This saltmarsh habitat is dominated by species Oryza coarctata. Visually higher densities of salt marsh were observed along the Salimpur and Sitakunda coasts. The salt marsh ecosystem of Chattogram coast supports diverse species, including shorebirds, mudskippers, horseshoe crabs, jellyfish, benthic organisms, crabs, shrimps, and fishes. We identified three spatial biodiversity clusters and Cluster 1 had the highest species diversity. This study found that the salt marsh ecosystem along the Chattogram coast serves as a habitat for over 50 salt marsh-associated fish species, which may depend on it for breeding, feeding, and nursery grounds. However, this area faces significant threats from activities such as burning, oil spills, shipbreaking, and fishing. Therefore, this study recommends an integrated approach to conserve the salt marsh ecosystem and its associated biota. This study serves as a unique example of an integrated monitoring strategy that supports conservation initiatives in developing countries.